The increase of O-acetylation and N-deacetylation in cell wall promotes acid resistance and nisin production through improving cell wall integrity in Lactococcus lactis. (1st September 2018) - Cao, Lijie; Liang, Dongmei; Hao, Panlong; Song, Qianqian; Xue, Ershu; Caiyin, Qinggele; Cheng, Zihao; Qiao, Jianjun
Abstract: Cell wall is closely related to bacterial robustness and adsorption capacity, playing crucial roles in nisin production in Lactococcus lactis . Peptidoglycan (PG), the essential component of cell wall, is usually modified with MurNAc O-acetylation and GlcNAc N-deacetylation, catalyzed by YvhB and XynD, respectively. In this study, increasing the two modifications in L. lactis F44 improved autolysis resistance by decreasing the susceptibility to PG hydrolases. Furthermore, both modifications were positively associated with overall cross-linkage, contributing to cell wall integrity. The robust cell wall rendered the yvhB/xynD -overexpression strains more acid resistant, leading to the increase of nisin production in fed-batch fermentations by 63.7 and 62.9%, respectively. Importantly, the structural alterations also reduced nisin adsorption capacity, resulting in reduction of nisin loss. More strikingly, the co-overexpression strain displayed the highest nisin production (76.3% higher than F44). Our work provides a novel approach for achieving nisin overproduction via extensive cell wall remodeling.